1994
DOI: 10.1042/cs0860015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Blood Flow during Intermittent Exercise: Comparison of the Microdialysis Ethanol Technique and 133Xe Clearance

Abstract: 1. Local skeletal muscle blood flow was monitored using the microdialysis ethanol technique and 133Xe clearance during intermittent isometric contractions (5 s on/10 s off) of the thigh at 0-60% of the maximal voluntary isometric contraction force. 2. A linear increase in blood flow over a 25-fold range was detected using both 133Xe clearance and the microdialysis ethanol technique. 3. The median correlation coefficient between percentage maximal voluntary isometric contraction force and the ethanol outflow/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 11 publications
0
62
0
Order By: Relevance
“…Changes in skeletal muscle blood flow were estimated with the ethanol outflow: inflow in ratio, and a decrease in muscle blood flow was also seen at the highest noradrenaline concentration. It should be noted, however, that the microdialysis-ethanol method can only delineate major changes (>50%) in blood flow rates [20]. Therefore, we may have missed a subtle, but significant, effect on blood flow rates at lower concentrations of noradrenaline.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes in skeletal muscle blood flow were estimated with the ethanol outflow: inflow in ratio, and a decrease in muscle blood flow was also seen at the highest noradrenaline concentration. It should be noted, however, that the microdialysis-ethanol method can only delineate major changes (>50%) in blood flow rates [20]. Therefore, we may have missed a subtle, but significant, effect on blood flow rates at lower concentrations of noradrenaline.…”
Section: Discussionmentioning
confidence: 98%
“…To estimate variations in tissue blood flow, ethanol was added to the perfusate solution as a flow marker [20]. Ethanol is not locally degraded, and does not affect tissue metabolism.…”
Section: Study Protocolmentioning
confidence: 99%
“…However, in the context of metabolic studies involving hyperinsulinaemia, especially with concurrent hypoglycaemia, where one would expect physiologic alterations in blood flow it is important to consider the potential influence that blood flow may have on the recovery of substrates by microdialysis. This issue was first raised when ethanol clearance from microdialysis perfusate was developed and validated [15] as a method of attaining a qualitative measure of local tissue blood flow at the site of microdialysis catheter insertion. Studies demonstrated that, in animals, gross changes in tissue blood flow alter the recovery of glucose by microdialysis [16] (i. e. an increase in local blood flow increases dialysate recovery of glucose) and similar findings have since been reported in human adipose and muscle tissues but with a less predictable effect of altered blood flow on the recovery of ECF lactate [17].…”
Section: Methodologic Considerationsmentioning
confidence: 99%
“…In rats, a number of studies have shown that microdialysis is applicable to this tissue bed [15,19,50] and we have used microdialysis in both skeletal muscle and adipose tissue ECF in humans. Our studies were firstly notable for the concentration gradients that exist for key metabolic substrates between the ECF compartment of both tissue beds and the circulation.…”
Section: Skeletal Musclementioning
confidence: 99%
“…Ethanol, which has been suggested to be metabolically inert in the muscle, is added to the perfusate and the ratio ethanol measured in the outflow (dialysate) : ethanol in the inflow (perfusate) has been proposed to be inversely correlated with the blood flow (Hickner et al 1992(Hickner et al , 1995. The microdialysis ethanol method has been validated against a 133 Xe-clearance method in rat skeletal muscle (Hickner et al 1994). However, the 133 Xe-clearance method is known to show a non-linear response and to have inherent methodological limitations, such as differences in tissue tracer solubility (Clausen & Lassen, 1971;Lassen et al 1983).…”
Section: Determination Of Local Blood Flow In Vivomentioning
confidence: 99%